Analysis of the Elite Sports Policy Framework in Iran - Pasban, Mohsen; Naderi Nasab, Mehdi; Biniaz, Seyyed Abbas (Health Nexus, 2025)
The purpose of the present study was to analyze the policy framework for elite sports in Iran. The research method is qualitative with a systematic analysis approach. The statistical population included all faculty members of physical education, managers, and experts from executive organizations, professional sports organizations, as well as scientific documents and resources. A sufficient sample was selected based on theoretical saturation through purposive and available sampling (16 individuals and 28 documents). Research tools included systematic library study and semi-structured interviews, and the validity of the tools was evaluated using qualitative validity assessment methods (content validity). Data were analyzed using coding and conceptual framework methods. The conceptual framework of elite sports policy in Iran was identified in 10 perspectives and is categorized into 5 conceptual levels: elite sports policy framework, the groundwork for implementing elite sports policies, the policy process for elite sports development, strategic maturity of the elite sports system, and the level of development and functions of elite sports. The framework presented in this research provides an understanding of the dimensions of policy development for elite sports based on its relationship with a set of different activities. Based on this framework, an objective evaluation of management activities in elite sports can be conducted, and scientific information regarding appropriate actions that sports organizations need to take for the development of elite sports policy can be provided.